2021
DOI: 10.15832/ankutbd.818397
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mars Data Mining Algorithm Based on Training and Test Sets in Determining Carcass Weight of Cattle in Different Breeds

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The difference can be attributed to the animal species. Çanga [ 33 ] mentioned that the MARS algorithm could allow livestock breeders to obtain effective clues by using independent variables such as breed, age and body weight in estimating hot carcass weight with the determination coefficient of 0.975. Şengül et al [ 34 ] mentioned that MARS and Bagging MARS algorithms revealed correct results according to the goodness-of-fit statistics, and it has been determined that the MARS algorithm gives better results in live weight modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The difference can be attributed to the animal species. Çanga [ 33 ] mentioned that the MARS algorithm could allow livestock breeders to obtain effective clues by using independent variables such as breed, age and body weight in estimating hot carcass weight with the determination coefficient of 0.975. Şengül et al [ 34 ] mentioned that MARS and Bagging MARS algorithms revealed correct results according to the goodness-of-fit statistics, and it has been determined that the MARS algorithm gives better results in live weight modeling.…”
Section: Discussionmentioning
confidence: 99%
“…To further optimize the target responses and to ensure optimum milk yield for the tested dependent variables, the YieldAutumn/winter/spring/summer estimation equations was first defined by looking at the MARS equation in Table 3. First of all, when the four prediction models are examined by looking at both Table 3 and the prediction equations, the sign differences regarding some coefficients of the same basic functions are remarkable (Akin et al, 2020b;Çelik and Yılmaz 2018;Çanga 2022;Çanga and Boğa, 2019). Since the threshold value for the lactation day, which is one of the variables discussed in Table 2, is LD=159, in the case of max(0, MDN -89), there is an increase of 16.16 units and 1.78 units in YieldAutumn and YieldSpring milk yield, respectively; Yieldwinter and Yieldsummer milk yields decreased by 9.36 and 4.02 units, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…MARS algorithm used by Friedman (1999) to capture nonlinear relationships between predictors and response variable(s) is a powerful approach that does not require assumptions about functional relationships between dependent and input variables. The model that emerges as the weighted total basic function including the BFi (x) function is given by Equation 1 below (Akin et al, 2020a;Eyduran et al, 2020;Çanga and Boğa 2020;Çanga 2022).…”
Section: Multivariate Adaptive Regression Spline (Mars)mentioning
confidence: 99%
“…The initial patterns that specify the smallest amount of the prediction model are abolished in the backward pass process, and this process is hand-me-down in the resolution to this problem [ 18 , 35 , 36 ]. The MARS algorithm is a significant instrument that can take linear and nonlinear relationships between dependent and independent variables [ 37 , 38 ]. The equation for MARS procedure utilized to predict body weight from explanatory variables is below.…”
Section: Methodsmentioning
confidence: 99%